2017
DOI: 10.1089/lap.2016.0178
|View full text |Cite
|
Sign up to set email alerts
|

Antireflux Versus Conventional Plastic Stent in Malignant Biliary Obstruction: A Prospective Randomized Study

Abstract: According to these results, the use of this ARS is not recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In all patients enrolled in this study, the median patency of this new ARPS was 285 d, which was significantly longer than 130 d observed for the TPS. Moreover, the median patency was also better than previously reported median ARPS patency times[1,11,12]. There were no side holes in either ARPS or TPS; this avoided the possibility of duodenal contents entering the bile duct to bypass the valve.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…In all patients enrolled in this study, the median patency of this new ARPS was 285 d, which was significantly longer than 130 d observed for the TPS. Moreover, the median patency was also better than previously reported median ARPS patency times[1,11,12]. There were no side holes in either ARPS or TPS; this avoided the possibility of duodenal contents entering the bile duct to bypass the valve.…”
Section: Discussionmentioning
confidence: 59%
“…This provided further evidence that duodenobiliary reflux may play another important role in stent occlusion. To our knowledge, only three studies[1,11,12] in the published English literature have focused on changing the design of PSs to eliminate retrograde flow from the duodenum, prolonging the duration of stent patency. Dua et al[11] in 2007 initially reported an ARPS with a 4 cm windsock-shaped tubular valve made of expanded polytetrafluoroethylene material attached to the duodenal end.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, 1 study suggested that anti-reflux stents had a shorter median patency of only 34 (8–49) days compared to a conventional stent patency of 167 (38–214) days. [29] The search for materials that inhibit microbial colonization, which likely contributes to stent obstruction, is ongoing, and experimental stents have been developed. [30,31] However, these innovative stents cannot yet be considered as definitive substitutes for conventional stents.…”
Section: Discussionmentioning
confidence: 99%